Comprehensive evaluation of the neuropeptide-Y gene variants in the risk of obesity - Zain, Shamsul Mohd; Mohamed, Zahurin; Jalaludin, Muhammad Yazid; Fauzi, F.; Hamidi, A.; Zaharan, Nur Lisa (Lippincott, Williams & Wilkins, 2015)
Background Orexigenic actions mediated by neuropeptide-Y (NPY) promote body weight regulation. Genetic variations in the NPY gene could therefore influence susceptibility to obesity, but results have been conflicting. We have carried out, for the first time, a case-control study to examine the effect of NPY rs16147 and rs5574 variants with the risk of obesity in Asians and also a meta-Analysis to summarize the effect of these variants including that of the widely studied rs16139. Materials and methods Genotypes and biochemistry data were determined for 942 children (262 cases and 680 controls) recruited from 23 randomly selected schools in Malaysia. Relevant articles were identified from Pubmed, Embase, Web of Science and Google Scholar. Data were extracted and summary estimates of the association between the NPY variants and obesity were examined. Results The frequency of the rs16147 T allele was significantly higher in the cases than controls (odds ratio 1.27, 95% confidence interval 1.04-1.55, P=0.022), whereas the rs5574 T allele was significantly higher in the controls (odds ratio 0.76, 95% confidence interval 0.61-0.96, P=0.020). In addition, NPY rs16147 was significantly correlated with obesity parameters including BMI, waist circumference, triglyceride and body fat percentage (P<0.05). Meta-Analysis including nine case-control studies further confirmed the findings of the association of the two variants with the risk of obesity and also found that rs16139 was associated with increased risk. Conclusion This study suggests that NPY rs16147 T and rs16139 C minor alleles are associated with increased risk, whereas the minor allele T of the rs5574 is associated with a reduced risk of obesity.